Aging Promotes Sirtuin 3–Dependent Cartilage Superoxide Dismutase 2 Acetylation and Osteoarthritis. Issue 8 (27th July 2016) - Fu, Yao; Kinter, Michael; Hudson, Joanna; Humphries, Kenneth M.; Lane, Rachel S.; White, Jeremy R.; Hakim, Michael; Pan, Yong; Verdin, Eric; Griffin, Timothy M.
Abstract : Objective: To quantify functional age‐related changes in the cartilage antioxidant network in order to discover novel mediators of cartilage oxidative stress and osteoarthritis (OA) pathophysiology. Methods: We evaluated histopathologic changes of knee OA in 10‐, 20‐, and 30‐month‐old male F344BN rats and analyzed cartilage oxidation according to the ratio of reduced to oxidized glutathione. Antioxidant gene expression and protein abundance were analyzed by quantitative reverse transcription–polymerase chain reaction and selected reaction–monitoring mass spectrometry, respectively. Superoxide dismutase 2 (SOD2) activity and acetylation were analyzed by colorimetric enzyme assays and Western blotting, respectively. We examined human OA cartilage to evaluate the clinical relevance of SOD2 acetylation, and we tested age‐related changes in the mitochondrial deacetylase sirtuin 3 (SIRT‐3) in rats and mice. Results: Cartilage oxidation and OA severity in F344BN rats increased with age and were associated with an increase in SOD2 expression and protein abundance. However, SOD2‐specific activity decreased with age due to elevated posttranslational lysine acetylation. Consistent with these findings, SIRT‐3 levels decreased substantially with age, and treatment with SIRT‐3 increased SOD2 activity in an age‐dependent manner. SOD2 was also acetylated in human OA cartilage, and activity was increased with SIRT‐3 treatment. Moreover, in C57BL/6J mice, cartilage SIRT‐3 expression decreased with age, and whole‐body deletion of SIRT‐3 accelerated the development of knee OA. Conclusion: Our results show that SIRT‐3 mediates age‐related changes in cartilage redox regulation and protects against early‐stage OA. These findings suggest that mitochondrial acetylation promotes OA and that restoration of SIRT‐3 in aging cartilage may improve cartilage resistance to oxidative stress by rescuing acetylation‐dependent inhibition of SOD2 activity.